2020
DOI: 10.1002/lsm.23249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fractional CO2 Versus Long Pulsed Nd:YAG Lasers in Treatment of Hypertrophic Scars and Keloids: A Randomized Clinical Trial

Abstract: Background Keloids and hypertrophic scars are challenging to both patients and physicians. They can be aesthetically disfiguring, functionally debilitating, and emotionally distressing. Lasers have introduced new mechanisms to improve scars both on aesthetic and symptomatic levels. Aim of Work Comparing the efficacy of fractional CO2 laser, long‐pulsed Nd:YAG laser and their combination in the treatment of hypertrophic scars and keloids on clinical, histopathological, and biochemical basis. Patients and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…This study would evaluate whether the fCO 2 laser is really superior to other lasers or if the lasers all entail similar effectiveness. A recently published study showed a slight superiority of the fCO 2 laser over a long pulsed Nd:YAG (neodymium‐doped yttrium aluminum garnet) laser in treatment of hypertrophic scars 19 . However, this study had not been conducted in the format of a split‐scar study.…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…This study would evaluate whether the fCO 2 laser is really superior to other lasers or if the lasers all entail similar effectiveness. A recently published study showed a slight superiority of the fCO 2 laser over a long pulsed Nd:YAG (neodymium‐doped yttrium aluminum garnet) laser in treatment of hypertrophic scars 19 . However, this study had not been conducted in the format of a split‐scar study.…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…A recent randomized control trial, concluded that fractional CO 2 laser treatment improved the VSS, increased dermal collagen and elastic fibers in hypertrophic and keloid scars compared to a long/pulse Nd:YAG laser 5 . In the case of combined treatments, Sabry et al 69 showed that there was a significant reduction in VSS 1 month after CO 2 laser monotherapy or CO 2 laser followed by topical 5‐fluorouracil (5‐FU) or verapamil with no significant side effects.…”
Section: Overview Of Fractional Lasersmentioning
confidence: 99%
“…Triamcinolone acetonide (TAC), 78–81 desoxymethasone 0.25%, 82 5‐FU, 5,83 betamethasone, 84 verapamil hydrochloride, 69 have all been applied over scars effectively in conjunction with lasers to overcome common side effects due to continuous subcutaneous use. In addition, comparisons between 5‐FU and topical corticosteroids have encountered similar clinical outcomes, but fewer dermal atrophy and telangiectasia occurrence for the 5‐FU LADD treatment 83 .…”
Section: Overview Of Fractional Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous advances involving surgical procedures, silicone gel sheets, steroid injections, and pressure therapy have helped to decipher the process of scar formation and wound healing; however, these therapies have had only limited effects. Recently, several attempts to apply the laser therapy for HTS treatment have been made [5,6]. For the first time, Alster [7] reported an average improvement of 57% after the first treatment and 83% after the second treatment with pulsed dye lasers (PDLs) for hypertrophic surgical and traumatic scars based on an overall clinical assessment scale.…”
Section: Introductionmentioning
confidence: 99%